2020
DOI: 10.1242/jcs.246363
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Mdm36 reveals Num1 foci that mediate dynein-dependent microtubule sliding in budding yeast

Abstract: Current model for spindle positioning requires attachment of the microtubule (MT) motor cytoplasmic dynein to the cell cortex, where it generates pulling force on astral MTs to effect spindle displacement. How dynein is anchored by cortical attachment machinery to generate large spindle-pulling forces remains unclear. Here, we show that cortical clustering of Num1, the yeast dynein attachment molecule, is limited by its assembly factor Mdm36. Overexpression of Mdm36 results in an overall enhancement of Num1 cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 52 publications
6
8
0
Order By: Relevance
“…6C). The Num1 assemblies present at the sites of cortical dynein anchoring were smaller and more diffuse than mitochondria-assembled Num1 clusters, consistent with previous descriptions of dynein anchoring by Num1 in the absence of mitochondria (Omer et al 2018;Omer et al 2020).…”
Section: Disrupting the Eflm In Full Length Num1 Can Rescue Dynein Function In The Absence Of Mitochondrial Inheritancesupporting
confidence: 90%
See 4 more Smart Citations
“…6C). The Num1 assemblies present at the sites of cortical dynein anchoring were smaller and more diffuse than mitochondria-assembled Num1 clusters, consistent with previous descriptions of dynein anchoring by Num1 in the absence of mitochondria (Omer et al 2018;Omer et al 2020).…”
Section: Disrupting the Eflm In Full Length Num1 Can Rescue Dynein Function In The Absence Of Mitochondrial Inheritancesupporting
confidence: 90%
“…Thus, mitochondria do not directly activate dynein activity or processivity per se, but instead help to arrange Num1 in clusters at the cell cortex that are competent to anchor dynein, and subsequently dynein is activated. As shown here in this study with the Num1 EFLM mutants and as is suggested by other studies that alter Num1 assembly (Omer et al, 2018(Omer et al, , 2020, it is possible to bypass the role of mitochondria in facilitating dynein anchoring in certain mutant conditions. However, in WT conditions, it is clear that the presence of mitochondria in the bud positively impacts dynein function in nuclear inheritance and this is dependent on a functional EFLM.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations